The fear of Islam : an introduction to Islamophobia in the West - Green, Todd H. (Fortress Press, 2015)
American and European societies, particularly in the long wake of the events of 9/11 and the bombings in Madrid and London, have struggled with the recurrent problem of Islamophobia, which continues to surface in waves of controversial legislative proposals, public anger over the construction of religious edifices, and outbreaks of violence. The ongoing conflict between Israel and Palestine contributes fuel to the aggressive debate in Western societies and creates the need for measured discussion about religion, fear, prejudice, otherness, and residual colonialist attitudes. The Fear of Islam speaks into this context, offering an introduction to the historical roots and contemporary forms of religious anxiety regarding Islam within the Western world. Tracing the medieval legacy of religious polemics and violence, Green weaves together a narrative that orients the reader to the complex history and issues that originate from this legacy, continuing through to the early and late modern colonial enterprises, the theories of "Orientalism," and the production of religious discourses of alterity and the clash of civilizations that proliferated in the era of 9/11 and the war on terror. The book contains analysis of interviews from figures such as Keith Ellison, John Esposito, Ingrid Mattson, Eboo Patel, Tariq Ramadan, and others